A Radiatively Driven Wind from the ηtel Debris Disk - Perez-Marquez, S (American Astronomical Society, 2021)
We present far- and near-ultraviolet absorption spectroscopy of the ∼23 Myr edge-on debris disk surrounding the A0V star η Telescopii, obtained with the Hubble Space Telescope Space Telescope Imaging Spectrograph. We detect absorption lines from C I, C II, O I, Mg II, Al II, Si II, S II, Mn II, Fe II, and marginally N I. The lines show two clear absorption components at −22.7 ± 0.5 km s−1 and −17.8 ± 0.7 km s−1, which we attribute to circumstellar (CS) and interstellar gas, respectively. CO absorption is not detected, and we find no evidence for star-grazing exocomets. The CS absorption components are blueshifted by −16.9 ± 2.6 km s−1 in the star s reference frame, indicating that they are outflowing in a radiatively driven disk wind. We find that the C/Fe ratio in the η Tel CS gas is significantly higher than the solar ratio, as is the case in the β Pic and 49 Cet debris disks. Unlike those disks, however, the measured C/O ratio in the η Tel CS gas is consistent with the solar value. Our analysis shows that because η Tel is an earlier type star than β Pic and 49 Cet, with more substantial radiation pressure at the dominant C II transitions, this species cannot bind the CS gas disk to the star as it does for β Pic and 49 Cet, resulting in the disk wind. © 2021. The American Astronomical Society. All rights reserved.